The effect of NPK fertilizer with different dosage on the growth rate seaweed (Caulerpa racemosa) - Riyadi Subur; Muhammad Irfan; Nebuchadnezzar Akbar (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
NPK is a type of fertilizer that plays a role in increasing growth and survival in plants such as seaweed. This study aims to determine the effect of different NPK fertilizer doses on the growth rate of seaweed (Caulerpa racemosa), and to determine which NPK fertilizer dosage has the best effect on the growth rate of C. racemosa. Research begins with collecting samples of seaweed in coastal waters. Ternate Island District Kastela, and the cultivation process is carried out on Jalan Jan, Tabona Village, South Ternate City. The time of the research was two months from August to October, 2020. This study used 12 units of cool box in the form of cork with a size of 90 x 30 cm, which is used as a container for maintaining of C. racemosa. In each treatment using a seed weight of 50 grams. The NPK fertilizer dosage treatment tested was 4 doses, with 3 replications, namely: treatment A: 40 ml NPK fertilizer; B: 60 ml NPK fertilizer; C: 80 ml NPK fertilizer; D: 0 ml NPK fertilizer (control). Research containers using random placement. The design used was a completely randomized design (CRD), using analysis of variance (ANOVA). The results obtained showed that NPK fertilizer with different doses the effect is not significantly different on the growth rate of C. racemosa with the highest average growth rate in treatment C amounting to 8.725%, followed by treatment B of 8.178%, treatment A of 7.761%, and the lowest was treatment D of 6.519%.Keywords:NPKSeaweedCaulerpa racemosaGrowth rate